Quick and easy preparation method for decoctions of kampo formula (part 3): Extraction efficiency of the IPCD method for volatile compounds. Issue 2 (October 2016) - Fueki, Tsukasa; Sumino, Megumi; Makino, Toshiaki; Matsuoka, Takanori; Beppu, Masashi; Tanaka, Koichiro; Namiki, Takao
ABSTRACT: Aim: The immersing powdered crude drugs (IPCD) method was developed as a quick, easy and high‐yield way to prepare decoctions. IPCD may be very useful for decoctions of crude drugs containing volatile compounds because it does not involve boiling. The aim of this study was therefore to test this hypothesis using cinnamon bark (the bark of the trunk of Cinnamomum cassia ) and perilla herb (the leaves and the tips of the branches of Perilla frutescens var. acuta ). Methods: The amounts of the marker compounds in the IPCD immersion prepared from cinnamon bark or perilla herb were measured and compared with those prepared with the conventional decoction method. Results: The amounts of cinnamaldehyde and perillaldehyde in the IPCD immersion per 1 g of crude drugs exceeded those in the conventional decoctions by two‐fold and 30‐fold, respectively. Conclusion: The IPCD method is outstanding for the decoction of crude drugs containing volatile compounds.